Inciting Climate Activism in "Secular-Spiritual" Spaces - Hautzinger, Sarah (Journal for the study of religion, nature and culture, 2026)
Coordinated, interfaith movements offer potential to mobilize civic engagement with the climate crisis and help break from decades of insufficient action. This account explores local to global climate organizing in "secular-spiritual" spaces, and its decompartmentalizing effects upon my roles as ethnographer/scholar, activist, and private person with a spiritual life. I first describe encountering Greenfaith International as an exemplar for organizing across geographical and interfaith lines, and including big-picture, mitigation-focused goals. Next, I recount scenes from subsequent efforts to engage regional inter-spiritual networks and individual groups whose shared "secular-spiritual" orientations made them good prospects for climate work: the Crestone Spiritual Alliance, Earth Church Circle, and All Souls Unitarian Universalist Church, all of southern Colorado. I argue that these "secular-spiritual", interfaith spaces hold distinctive potential for ethnically and morally based climate advocacy and climate-movement building. Nonetheless, the essay concludes by considering ways climate work is singularly confounding, humbling, and easily deflected onto other forms of justice work.